Business in practice: analysis of value drive´s performance in the era of electrification and personal reflection - Kühnel, Daniel Ulrich (2024)
This paper reviews the strategic, operational, and financial performance of ValueDrive Motors, a company managed within NOVA SBE’s BiP business simulation. The first section is a data driven business analysis. It analyzes the strategy aimed at producing high-quality electric vehicles at low cost alongside departmental performance of Operations and Finance, focusing on metrics they could impact in the simulation. The second section is a personal reflection, highlighting two critical incidents, a humbling lesson and a low-performing colleague, that contributed to the author’s leadership and teamwork development. These reflections emphasize the importance of collective decision-making, trust-building, and adaptability in team dynamics.